2003
DOI: 10.1002/cncr.11775
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenetic therapy with pioglitazone, rofecoxib, and metronomic trofosfamide in patients with advanced malignant vascular tumors

Abstract: The processing–property relationship of a model cryogenically mechanically alloyed polymer–polymer system [polycarbonate (PC) and poly(aryl ether ether ketone) (PEEK)] was investigated. PC and PEEK powders were cryogenically mechanically alloyed for 10 h, and the resulting two‐phase powder particles were processed into testable coupons with a miniature ram‐injection molder. The bulk mechanical properties of the coupons made from the mechanically alloyed powders and nonmechanically alloyed powders were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
98
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 27 publications
0
98
1
5
Order By: Relevance
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 97%
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 97%
“…Although in preclinical studies TZD showed antiproliferative, pro-apoptotic, and differentiating effects, their use in clinical trials planned for the treatment of limited cohorts of patients affected by different types of solid tumors gave controversial and not encouraging results (Demetri et al 1999, Debrock et al 2003, Vogt et al 2003, Reichle et al 2004, Smith et al 2004, Yee et al 2007, Read et al 2008. Indeed, only a few studies found TZD to exert some positive therapeutic effect, particularly if combined with chemotherapic and angiostatic drugs (Vogt et al 2003, Reichle et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only a few studies found TZD to exert some positive therapeutic effect, particularly if combined with chemotherapic and angiostatic drugs (Vogt et al 2003, Reichle et al 2004. This is of particular notice, since RGZ has been demonstrated to inhibit primary tumor growth and metastasis in different xenograft tumors through suppression of angiogenesis (Panigrahy et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Antiangiogenic properties for Tzds and PPARg agonists have been described in preclinical models (Xin et al, 1999;Panigrahy et al, 2002;Margeli et al, 2003) and a clinical trial (Vogt et al, 2003). These effects may be mediated through both PPARg-dependent and -independent pathways depending upon concentration of PPARg agonist and tumor cell type.…”
Section: Discussionmentioning
confidence: 99%